Vaccine Platforms: Biosynthesis of Self‐Assembled Proteinaceous Nanoparticles for Vaccination (Adv. Mater. 42/2020). Issue 42 (20th October 2020) - Pan, Chao; Wu, Jun; Qing, Shuang; Zhang, Xiao; Zhang, Lulu; Yue, Hua; Zeng, Ming; Wang, Bin; Yuan, Zheng; Qiu, Yefeng; Ye, Huahu; Wang, Dongshu; et al.
Abstract : In article number 2002940, Li Zhu, Wei Wei, Guanghui Ma, Hengliang Wang, and co‐workers present a Nano‐B5 vaccine platform that is fully bio‐synthesized in bacteria. This self‐assembled platform serves as a versatile chassis to combine adjuvant modular and display peptide or polysaccharide antigens. Upon excellent lymph‐node targeting and immunoresponse elicitation in vivo, strong prophylactic effects and efficient therapeutic effects are achieved.